Product design – Molecules, devices, functional products, and formulated products - Gani, Rafiqul; Ng, Ka M. (Computers & chemical engineering, 2015)
•Challenges to advances in product design have been identified.•Chemical products have been classified by market sector and by product type.•Design of single molecules and molecular blends has been thoroughly reviewed.•An integrated experiment-modeling approach to the design of formulated products has been explained and illustrated.•The approach to the design of chemical devices and functional products has been formulated. Chemical product design is a multidisciplinary and diverse subject. This article provides an overview of product design while focusing on product conceptualization. Four product types are considered – molecular products, formulated products, devices and functional products. For molecular products, computer-aided design tools are used to predict the physicochemical properties of single molecules and blends. For formulated products, an integrated experiment-modeling approach is used to generate the formula with the specified product attributes. For devices and functional products, conceptual product design is carried out by modeling the product based on thermodynamics, kinetics and transport processes, by performing experiments, and by decision making based on rule-based methods The results are product specifications in terms of the type of ingredients, composition, and the structure, form, shape or configuration of the product.